A clinical case of extragastrointestinal tumor in combination with testicular feminization syndrome (Morris syndrome) - Z. A. Sidakova; A. A. Baranova; A. N. Gritsai; G. D. Efremov; L. N. Lyubchenko (Сибирский онкологический журнал, 2023)
Background. According to literature data, errors in the diagnosis of gastrointestinal tumors (GIST) are uncommon, accounting for approximately 6% of cases that results in treatment failure. Case report. Here, we describe a rare case of a 58-year-old female patient with extragastrointestinal stromal tumor (EGIST) in the evidence of testicular feminisation syndrome (TFS) – Morris syndrome. This hereditary pathology is associated with complete insensitivity of target organs to androgens and was described in 1953 by the American gynaecologist John Morris. The patient was referred to the cancer clinic, where she was wrongly diagnosed with uterine leiomyoma. Interdisciplinary approach, cancer alarm, active surgical tactics, additional immunohistochemical (IHC) and molecular genetic studies (MGI) allowed verifcation of the true diagnosis. There are reported cases of EGIST of the bladder, prostate, retroperitoneum, mesentery, omentum, and posterior mediastinum. However, we were not able to fnd publications regarding the cases of EGIST originating from the vaginal wall. Combination of TFS and EGIST is a unique case in our clinical practice. Conclusion. The study of rare cases expands the understanding of the molecular pathogenesis of malignancies. Patients with rare types of malignant tumors should be obligatorily examined and treated in specialized cancer clinics with involvement of certifed oncologists, surgeons, chemotherapists, geneticists.